(3QSGdI GdMhQ GdYjf hJaSjQgGs - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s ((3CMeO Hf MSf Hf Ydi GHf eMeO Hf Ydi GdSHYi s)
(3ChdgG (B:s
(3CeG HYO MeOddg GdPi GSJhLH GdMeO HcQe hLhOg hChLH GdeRjO def TcQ ef YHjOg, aEf GdGOH UGQ HVGYg ai gPG GdhbJ eVGYI s
(3BNQgG (B:s
(3GdLOjQ GdMbjbi HGdTF ,jbGd adGf LOjQ HcPG hbejf Hg hMQi Hg, hNdjb Hg, hMbjb Hg s
(3hQO ai GdeNWhW CfgG QSGdI hYOgG GdCYdGe ef cJH fThGf hde jPcQ GfgG QSGdIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs